36.3k views
16 votes
If f(x)=x/3 -2 and g(x)=3x^2+2x-6 find (f+g)(x)

User Chester
by
4.6k points

1 Answer

6 votes

Answer:

(f + g)(x) = 3x² + (7/3)x - 8

Explanation:

To find (f + g)(x), you need to add both the f(x) and g(x) equations together.

f(x) = x/3 - 2 ..... which is equal to ... f(x) = (1/3)x - 2

g(x) = 3x² + 2x - 6

(f + g)(x) = ((1/3)x - 2) + (3x² + 2x - 6) <----- Add both equations

(f + g)(x) = 3x² + (1/3)x + 2x - 2 - 6 <----- Rearrange (2 = 6/3)

(f + g)(x) = 3x² + (7/3)x - 8 <----- Simplify similar terms

User RiverHeart
by
5.2k points